Didactic unit aimed towards educators for teaching english to students in 5th and 6th grades of the multigrade school of El Calvario, Bugaba 2011 - Ortega, Berta (UDELAS, 2011)
This project is attempting to show some different and creative ways that teachers can use to teach students using didacaatic guides ar El Calvario Multigrade School.